Demography of the ecosystem engineer Crassostrea gigas, related to vertical reef accretion and reef persistence. (5th March 2015) - Walles, Brenda; Mann, Roger; Ysebaert, Tom; Troost, Karin; Herman, Peter M.J.; Smaal, Aad C.
Abstract: Marine species characterized as structure building, autogenic ecosystem engineers are recognized worldwide as potential tools for coastal adaptation efforts in the face of sea level rise. Successful employment of ecosystem engineers in coastal protection largely depends on long-term persistence of their structure, which is in turn dependent on the population dynamics of the individual species. Oysters, such as the Pacific oyster ( Crassostrea gigas ), are recognized as ecosystem engineers with potential for use in coastal protection. Persistence of oyster reefs is strongly determined by recruitment and shell production (growth), processes facilitated by gregarious settlement on extant shell substrate. Although the Pacific oyster has been introduced world-wide, and has formed dense reefs in the receiving coastal waters, the population biology of live oysters and the quantitative mechanisms maintaining these reefs has rarely been studied, hence the aim of the present work. This study had two objectives: (1) to describe the demographics of extant C. gigas reefs, and (2) to estimate vertical reef accretion rates and carbonate production in these oyster reefs. Three long-living oyster reefs (>30 years old), which have not been exploited since their first occurrence, were examined in the Oosterschelde estuary in the Netherlands. A positive reef accretion rate (7.0–16.9 mm year −1 shell material) was observed, consistent with self-maintenance and persistent structure. We provide a framework to predict reef accretion and population persistence under varying recruitment, growth and mortality scenarios. Graphical abstract: Highlights: A positive reef accretion rate, resulting in self-maintaining persistent reefs. Accretion rates well in excess of sea level rise. Reef accretion rates and carbonate production in the range reported for coral reefs.